Typification of some Species of Sloanea (Elaeocarpaceae) - Sampaio, Daniela; Souza, Vinicius Castro (Phytotaxa, 2014)
Sloanea L. is the largest genus of Elaeocarpaceae in the New World and their species occurs from Mexico to Southern of Brazil. During the revision of the genus that we made for extra-Amazonian region of Brazil it was detected the need to organize its nomenclature, carried out in the present study which resulted in 48 valid names, 15 lectotypes here designated, 4 new synonyms and one illegitimate name. Additional comments on the genus, its geographical distribution, habitat type and season of flowering and fruiting are also provided.